Synthesis of Fe3O4 at different reaction temperatures and investigation of its magnetic properties on giant magnetoresistance (GMR) sensors for bio-detection applications - Antarnusa, Ganesha (Journal of Magnetism and Magnetic Materials, 2022)
Magnetite (Fe3O4) nanoparticles with different reaction temperatures (TR = 40, 60 and 80◦C) for the application of bio-detection have been successfully synthesized using the co-precipitation method. The average crystallite sizes of samples increased with the increase of TR and all samples showed high crystallinity with an inverse spinel cubic structure. The grain size increased with the increase of TR. On the other hand, all samples have polycrystalline structure and the brightest intensity at Miller’s index (311). From the results of the vibrating sample magnetometer (VSM) analysis, it was found that there was an increase in magnetic properties such as Hc, Mr and Ms along with the increase reaction temperature. For example, the saturation magnetization increased with the increase of TR. Next, the giant magnetoresistance (GMR) biosensor was explored by using an exchange-biased GMR sensor with the Wheatstone bridge method to detect Fe3O4 with variations of reaction temperature in an alcohol solution of 50 μg/ml. A DC in-plane magnetic field was used for this measurement. It was found that the Vout curve is sensitive to the presence of Fe3O4 and the maximum Vout appears at 2.8 Oe by applying an external field to the sensor of ± 95 Oe. The Vout difference increased with the increase of reaction temperature, which can be attributed to higher saturation magnetization, causing more difficult fringing of the magnetic field. The relationship between TR and |ΔV| is |ΔV| = 0.0175x + 0.49, in which |ΔV| linearly increases with the increase of reaction temperature. This study demonstrates the feasibility of Fe3O4-based detection using a GMR sensor and Fe3O4 as magnetic labels will be useful for potential bio-detection applications.